Activities of Cayratia trifolia Fruit on Oxidative Stress and Histological Change in Physical Stress-Induced Mice - Rousdy, Diah Wulandari; Wardoyo, Elvi Rusmiyanto Pancaning (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Lakum fruit (Cayratia trifolia L. Domin) contains secondary metabolite compounds that have antioxidant properties. C trifolia belongs to the Vitaceae family, known as tropical grapes that have a sweet and itchy taste. This study aims to determine the potential of C. trifolia fruit methanol fraction as an antioxidant based on the parameters of malondialdehyde levels, superoxide dismutase enzymes, SGOT enzymes, SGPT enzymes, kidney and liver histology. The study used 24 male Swiss mice which were divided into 6 treatments, namely normal control, negative control, positive control (vitamin E), and C. trifolia methanol fraction 115; 230; 460 mg/kgBW. Physical stress induction was given in the form of fasting and swimming for 5 days. The data were analyzed by one-way ANOVA and descriptive analysis for histological parameters. The results showed that the methanol fraction of 115 mg/kg BW decreased the best levels of malondialdehyde serum (38 µM), SGOT (34.7 U/L) and SGPT (34.6 U/L) compared to other doses. Doses of 115 mg/kgBW also provided the best levels of the superoxide dismutase enzymes (1.73 U/L) almost equal to vitamin E as positive control. Observations of kidney and liver histology showed a decrease in damage to hepatocytes and renal glomerulus in the 115 mg/kgBW C. trifolia methanol fraction. This research contributes to the development of C. trifolia as a natural antioxidant.